2010
DOI: 10.1002/cjce.20383
|View full text |Cite
|
Sign up to set email alerts
|

Study on corrosion rate of carbon steel pipe under turbulent flow conditions

Abstract: The effect of time (or corrosion products formation) on corrosion rate of carbon steel pipe in aerated 0.1 N NaCl solution under turbulent flow conditions was investigated. Tests were conducted using electrochemical polarisation technique by determining the limiting current density of oxygen reduction in Reynolds number (Re) range of 15 000 to 113 000 and temperature range of 30-60 • C. The effect of corrosion products formation on the friction factor increase was studied and discussed. Empirical correlations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 18 publications
(37 reference statements)
1
21
0
Order By: Relevance
“…This means that the deposition of oil on the surface is slight and does not restrain the heat transfer. The decrease of R f with time has also been noticed by Emani et al and a negative fouling resistance has also been reported by several workers for scale fouling and for crude oil fouling . The case of negative fouling resistance has been studied and discussed in detail in the work of Crittenden and Alderman .…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…This means that the deposition of oil on the surface is slight and does not restrain the heat transfer. The decrease of R f with time has also been noticed by Emani et al and a negative fouling resistance has also been reported by several workers for scale fouling and for crude oil fouling . The case of negative fouling resistance has been studied and discussed in detail in the work of Crittenden and Alderman .…”
Section: Resultsmentioning
confidence: 57%
“…This causes and increase in the heat transfer coefficient and thus a reduction in the fouling thermal resistance. It was found by several previous workers that the increased roughness due to fouling causes an increase in the heat transfer coefficient and a reduction the fouling resistances …”
Section: Resultsmentioning
confidence: 99%
“…This is due to the increased anodic polarization and a possibility of passivation. The clear increase of the corrosion rate with temperature is ascribed to two main reasons [5,8]: the first one is the increased anodic dissolution reaction of metal due to the decrease in activation energy of anodic reaction. The second one is the increased oxygen diffusivity that leads to increase the arrival of oxygen to the metal surface and hence enhance the corrosion.…”
Section: Results and Discussion 31 Free Corrosionmentioning
confidence: 99%
“…During each experimental run, the variation of galvanic potential with time was measurement by using Saturated Calomel Electrode SCE bridged by a Luggin capillary at a distance of 1-2 mm from the working electrode [8] connected to personal computer for data recording. The specimens were immersed in the acid solution for 1 h. During this time period, the galvanic current and galvanic potential were measured with time.…”
Section: Experimental Workmentioning
confidence: 99%
“…CS, leading to a decrease in the arrival of the cathodic species to the CS. Therefore, the oxidation rate of CS is decreased causing a decrease in I g (Slaiman and Hasan, 2010). An XRD analysis of the formed corrosion product layer showed that this layer consisted mostly of iron carbonate scale (FeCO 3 ).…”
Section: Samplementioning
confidence: 97%